Dome-shaped nanostructured wide-bandgap perovskite for tandem solar cell applications - Salem, Ahmed Fathi; Hameed, Mohamed Farhat. O.; Abdelhamid, Hamdy; El-Rabaie, Sanaa M.; Obayya, S. S. A.; El-Bashar, R. (Frontiers in Physics, 2026)
The development of wide-bandgap perovskite materials has enabled new opportunities for highly efficient tandem solar cell applications. In this study, the optical and electronic performance of a single junction dome-shaped nanostructured wide-bandgap perovskite (MA0.9Cs0.1Pb(I0.6Br0.4)3) is studied for all-perovskite tandem solar cell (SC) applications. The optical performance of the proposed design is studied using finite difference time domain. The introduction of the dome-shaped (Al2O3) antireflective layer improves the light absorption to 90.1% relative to 77.1% for the PSC without antireflective coating (ARC). Therefore, the maximum power conversion efficiency (PCE) of 15.3% is reported for the optimized structure (Eg = 1.82 eV) with an enhancement of 19.5% compared to the reference cell. When the defect density is increased to 1018 cm-3, the PCE is dropped to 7.7% with a reduction of 49.7% relative to the studied good practical defect density of 1015 cm-3. Furthermore, the impact of the perovskite bandgap on the electrical parameters of the perovskite solar cells (PSCs) device is analyzed. The optimized structure with a bandgap of 1.9 eV shows the highest PCE of 16.1% with a JSC of 18.1 mA/cm2. The results show that the presence of Al2O3 ARC enhances the performance of PSC, which can be useful for tuning wide-bandgap perovskite in tandem photovoltaic systems.